Environmental impact assessment of nutritional guidelines under organic agriculture in Switzerland - Crosnier, Agathe; Baudry, Gino; Jeangros, Laurence; Thalmann, Philippe (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe implementation of “farm to fork” solutions, taking into account the entire food value chain, is necessary to address the wide range of issues arising from agri-food systems. On the production side, organic farming is one of the main alternatives proposed. However, the interactions between the expansion of organic agriculture and the generalization of dietary changes according to dietary guidelines at the country level have not yet been considered.MethodsThis paper presents a commodity-based modeling of Swiss domestic food production in 2050, derived in four scenarios to compare the environmental impacts of organic and business-as-usual production as well as of two dietary guidelines, namely the EAT-Lancet and the Swiss Food Pyramid. A Life Cycle Assessment approach is then used to assess the environmental impacts through climate, ecosystems, soil and resource depletion.ResultsAll scenarios showed lower impacts compared to the current situation projected for 2050, mainly due to dietary changes. Despite lower yields, 100% organic production remains feasible if combined with dietary changes. Organic farming can be more impactful than conventional farming.DiscussionThe results highlight that the implementation of the best diet and alternative production method may trigger unforeseen interactions and emphasize the need for a systemic approach.